How Malay proverbs encode and evaluate emotion? a paremiological analysis - Lim, Kim Hui (Universiti Kebangsaan Malaysia, 2010)
It should be understood that peribahasa (Malay proverbs) normally performs different roles in Malay discourses, viz. literary, didactic or argumentative function. However, as proverb is presented in natural language, it also encodes and decodes the emotion of the people, the hati budi, hence representing the non-logical elements of the Malay mind. Using Norrick‟s studies on American proverbs as a reference, this paper examines and portrays the existence of the markers of affect in Malay proverbs. The author also explores the role of hati in the Malay proverbs and how the metaphors of hati and other body parts symbolism as found in the Malay proverbs are in line with three integrated aspects of human feelings, viz. language, culture and body, suggested by Kövecses